Implementasi Pembelajaran Berbasis Kecerdasan Buatan di Sekolah Dasar - Purnama, Purnama; Muharani, Irma Nur; Patras, Yuyun Elizabeth (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research is motivated by the low motivation and learning outcomes of students in elementary schools and aims to determine trends in artificial intelligence-based research and implementation as well as the influence of artificial intelligence on students' motivation and learning outcomes in elementary schools. The research method used is the SLR method by the PRISMA. This research was conducted through the PoP application with the database used is Google Scholar 2018-2023 with the keyword "artificial intelligence, elementary school". The subjects of this study are articles that have screening and have been included. The stages of research was identification, screening, Eligibility Process, include, and analysis. The collection technique uses excel application analysis table. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The results of this study show that the kecenderungand of research on AI in elementary schools 2018-2023 found that the number of article publications in that span of years has increased, while the number of citations applies the opposite. The use of AI applications can significantly improve the motivation and students learning outcomes.